Clinical challenges in the management of vaginal prolapse - Siddiqui NY; Edenfield AL (Dove Medical Press, 2014)
Nazema Y Siddiqui, Autumn L EdenfieldDivision of Urogynecology and Reconstructive Surgery, Duke University Medical Center, Durham, NC, USAAbstract: Pelvic organ prolapse is highly prevalent, and negatively affects a woman’s quality of life. Women with bothersome prolapse may be offered pessary management or may choose to undergo corrective surgery. In choosing the most appropriate surgical procedure, there are many factors to consider. These may include the location(s) of anatomic defects, the severity of prolapse symptoms, the activity level of the woman, and concerns regarding the durability of the repair. In many instances, women and their surgeons are challenged to weigh the risks and benefits of native tissue versus mesh-augmented repairs. Though mesh-augmented repairs may offer better durability, they are also associated with unique complications, such as mesh erosion. Furthermore, newer surgical techniques of mesh placement via abdominal or vaginal routes may result in different outcomes compared to traditional techniques. Biologic grafts may also be considered to improve durability of a surgical repair, while avoiding potential complications of synthetic mesh. In this article, we review many of the clinical challenges that gynecologic surgeons face in the surgical management of vaginal prolapse. Furthermore, we review data that can help guide decision making when treating women with pelvic organ prolapse.Keywords: pelvic organ prolapse, vaginal prolapse, surgery, sacrocolpopexy, sacrospinous ligament fixation, transvaginal mesh, uterosacral ligament suspension